2020
DOI: 10.1371/journal.pone.0242190
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of microRNA 182 and microRNA 18a in locally advanced triple negative breast cancer

Abstract: Background The study assessed the epigenetic regulation and the role of microRNA (miR) expression in locally advanced triple negative breast cancers (TNBC) and comparison with the clinico-pathological variables and survival. Methods Fifty patients of locally advanced TNBC during the period 2011–2013 were included. Expression level of test microRNA (miR-182 and miR-18a) was determined using Taqman quantitative Real time polymerase chain reaction (qRT-PCR) from formalin fixed paraffin embedded biopsy blocks. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The clinicopathologic analyses revealed that the expression level of miR-182-5p associates with larger tumor size, lymph node metastasis, and higher histologic grade in the BC patients. These results, in accordance with previous reports [ 46 48 ], imply the oncogenic roles of miR-182-5p in BC.…”
Section: Discussionsupporting
confidence: 93%
“…The clinicopathologic analyses revealed that the expression level of miR-182-5p associates with larger tumor size, lymph node metastasis, and higher histologic grade in the BC patients. These results, in accordance with previous reports [ 46 48 ], imply the oncogenic roles of miR-182-5p in BC.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, miR-182-5p could promote the proliferation, migration and angiogenesis of HUVECs. Consistently, the expression of miR-182 has shown a dramatic overexpression in breast cancer tissue samples (Barsoum et al 2020 ), and moreover, its overexpression significantly relates to poor clinical and pathological tumor characteristics in patients with locally advanced triple negative breast cancer and thus can be used as a tool to predict the outcomes and prognosis in these patients (Bajaj 2020 ). Downregulation of miR-182-5p contributes to inhibition of cell proliferation and promotion of tumor cell apoptosis by impairing the TLR4/NF-κB signaling pathway activity and increasing FBXW7 expression (Wu et al 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…The information about the reproducibility of serum or plasma analysis is inconsistent. The study by Mitchell et al suggests that the quantification of miRs in plasma and serum are correlated and that the analysis of miRs from plasma or serum are therefore reliable sources of sampling [ 52 ]. However, other studies have shown that miR expression is different according to the origin of the sample (plasma or serum).…”
Section: Discussionmentioning
confidence: 99%
“…MiRs have been proven to be stable markers and resistant to RNase activity and environmental factors. In a study by Mitchell et al [ 52 ], miR levels did not change when modifying the temperature of the samples (room temperature incubation for up to 24 h or freeze–thawing for up to 8 cycles). It was also shown that endogenous miRs were resistant to RNase activity, whereas exogenous miRs were rapidly degraded when introduced.…”
Section: Discussionmentioning
confidence: 99%